Runaway romances : Hollywood's postwar tour of Europe - Shandley, Robert R. (Temple Univ. Press, 2009)
Examines Hollywood's European travelogue romances from 1947 to 1964, the end of American isolationism and the advent of challenges in Hollywood that made American filmmakers begin filming abroad.
Keywords: Motion picture industry -- United States -- History.; Motion picture industry -- Production and direction -- United States -- History.; Motion pictures, American -- Europe -- History.; Love in motion pictures.; Travel in motion pictures.; Cinéma américain -- Europe -- Histoire.; Amour au cinéma.; Voyage au cinéma.; Cinéma -- Industrie -- États-Unis -- Histoire.; BUSINESS & ECONOMICS -- Industries -- Media & Communications.; TECHNOLOGY & ENGINEERING -- Telecommunications.; PERFORMING ARTS -- Film & Video -- History & Criticism.; Love in motion pictures; Motion picture industry; Motion pictures, American; Travel in motion pictures; Europe; United States; Filmwirtschaft; Liebesfilm; Reise -- Motiv; Europa; USA; Travelogue romances; History